CHARACTERISTIC ANALYSIS AND RELIABILITY MODELING PRINCIPLE OF GEAR TRANSMISSION SYSTEM - XIE LiYang (Jixie qiangdu)
Gear transmission system is a series system. However,it is different from the traditional series system in many aspects such as the relationship between system and elements,the manner for the system functioning,the time-dependent system configuration,etc. System classification is discussed firstly to meet the demand of system reliability modeling. For the purpose of system reliability analysis,a gear transmission system is taken as a time-dependent varying configuration system,which is different from the traditional series system with changeless configuration in space. According to different function,different configuration and different load characteristics,specific system oriented reliability analysis and modeling method are studied.Taking simple gear transmission system as an example,several system reliability models are developed,the reliability variation with load number and the differences between the new model and traditional model are illustrated.